Delamination damage of carbon fiber-reinforced polymer composite laminates under cyclic shear-induced loading conditions - Abdullah, Muhammad A’imullah (2018)
Interface delamination is a major failure mode induced by in-plane shear stress frequently encountered in carbon fiber-reinforce polymer (CFRP) composite laminates structures. This failure process under monotonic loading has been successfully described using cohesive zone model (CZM). Many previous CZM approaches for cyclic case were considering damage parameters based on a crack growth relation which has some disadvantages for predicting a non-linear crack growth. In addition, the previous CZM approach lacks ground in understanding the physics underlying the delamination process and effect of stress ratio. The objective of the study is to extend the existing CZM to account for the delamination damage evolution of CFRP composite laminates under cyclic shear-induced loading conditions named as cyclic cohesive zone model (CCZM). In this respect, the fatigue damage response and the residual interfacial properties associated with the development of the CCZM are established under cyclic shear-induced loading condition. A series of Mode-II-type tests were performed on prefatigued